The Battle for Urban Space: Dynamics of Spatial Change In Siak, Riau, Indonesia - Amady, M. Rawa El; Purnama, Dadang Hikmah; Arianti, Yosi (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
This study aims to examine the implications of changes in urban space as a result of the implementation of government policies in the development and expansion of the city of Siak on the existence of community space and how the community seizes and utilizes spaces of the industry and government to maintain their subsistence economic life. This study uses a rapid ethnography approach. Researchers conduct a desk study before fieldwork to obtain an initial research report. Researchers stayed in Siak District for 40 days to conduct observations, in-depth interviews, informal conversations, and stakeholder discussions. We conducted Focus Group Discussions (FGD) in the four research villages. The event was attended by 28 participants from four villages, comprising village heads, homemakers, peasants, small traders/street vendors, freelance workers, and NGOs at the district level. The study shows that the four research villages have changed from subsistence community spaces to industrial and government spaces. In this research, the community space is becoming increasingly limited, so people carry out two strategies in seizing industrial and government spaces, namely using government spaces to become places for work and business and controlling industrial spaces, Even though this can give rise to latent and manifest tenure conflicts, corporate and society's urban space becomes an arena for struggling for the means of production represented through control and ownership of space. Society must adapt to these conditions to obtain space for them. Government policies in developing and expanding the city of Siak have not taken the community's interests as the primary goal.